Low-energy-consumption long-service-life titanium-based multi-component composite anode and preparation method thereof
By introducing a dense TiTa layer and Nd-Sb-SnO2 layer into the titanium-based lead dioxide anode and adding a multi-component active layer of Bi-Co3O4-MnO2, the problems of easy shedding on the anode surface, poor conductivity, high energy consumption and short life are solved, and the stability and catalytic activity are improved and the energy consumption is reduced.
Patent Information
- Application Number
- CN202411636687.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
During the use of nonferrous metal electroplasia, the existing titanium-based lead dioxide anode has problems such as easy surface coating, poor conductivity, high energy consumption and short life.
Through the introduction of the dense TiTa layer and the Nd-Sb-SnO2 layer, a multi-layer intermediate layer is formed to increase the Bi-Co3O4-MnO2 multi-component modified active layer, improve the stability and catalytic activity of the anode and reduce the oxygen evolution potential.
It significantly enhances the stability and catalytic activity of the anode, improves the binding force between the anode and the coating, reduces energy consumption, and extends the service life of the anode.
Smart Images

Figure CN119506979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metal electrochemical metallurgy, and specifically relates to a low-energy-consumption and long-life titanium-based multi-component composite anode and a preparation method thereof. Background Art
[0002] The anode material in the electrochemical metallurgical electrowinning process of non-ferrous metals not only directly affects the power consumption and electrode life, but also has a great impact on the quality and output of the cathode product. At present, the anodes used in the electrowinning process are traditional lead-silver alloy anodes and insoluble titanium-based lead dioxide anodes. The traditional lead-based alloy anodes have the problems of high power consumption, severe corrosion and deformation, easy lead contamination of cathode products, a lot of anode mud, and low tolerance to fluorine and chlorine. The insoluble titanium-based lead dioxide anode has the advantages of stable shape and size, light weight, no anode mud, not easy to bend and deform, and strong tolerance to fluorine and chlorine. Therefore, the insoluble titanium-based anode is more and more widely used in the field of electrochemical metallurgy. However, the insoluble titanium-based lead dioxide anode will have the following problems during the use of non-ferrous metal electrowinning: (1) The surface coating is not tightly bonded to the substrate, and the coating is easy to fall off; (2) The conductivity is poor and the cell pressure is high, which increases the energy consumption during use; (3) The internal stress is large, the stability is poor, and the service life is short. Therefore, it is necessary to improve the catalytic activity and service life of titanium-based lead dioxide through coating material design and reduce its oxygen evolution overpotential.
[0003] The patent application document with publication number CN201710966737.2 discloses "Titanium-based lead dioxide / manganese dioxide gradient anode for zinc electrowinning and preparation method thereof", which improves the corrosion resistance of the anode and the quality of the cathode product by depositing a silver-doped manganese dioxide layer on a porous composite lead dioxide conductive layer. However, the anode life is short due to the weak bonding force between the lead dioxide layer and the manganese dioxide layer.
[0004] The patent application document with publication number CN202111267586.4 discloses "a titanium-based gradient lead dioxide composite electrode material for copper electrowinning and a preparation method thereof", which constructs Sn-Ru-Ta-ZrO x The titanium-based gradient lead dioxide composite electrode material is composed of an oxide bottom layer, a β-PbO2-nano SnO2 middle layer, an α-PbO2-copper coated graphite powder transition layer and a β-PbO2-nano ZrN-cobalt coated hollow glass microsphere active layer, which improves the current efficiency and service life of the anode. However, due to the complex components between the gradient layers and the long process flow, the electrode catalytic activity and stability are poor. Summary of the invention
[0005] In order to overcome the technical problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a low-energy consumption and long-life titanium-based multi-component composite anode and a preparation method thereof. By introducing a dense TiTa layer and a Nd-Sb-SnO2 layer, the passivation of the anode titanium substrate is avoided; the introduction of a Bi-Co3O4-MnO2 multi-component modified active layer increases the service life of the anode while reducing the oxygen evolution potential of the anode. The composite anode can significantly enhance the stability and catalytic activity of the anode, improve the bonding force between the substrate and the coating, improve the current efficiency during the use of the anode, and reduce the energy consumption during the use of the anode.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a multi-layer intermediate layer, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the multi-layer intermediate layer comprises, from bottom to top, a TiTa intermediate layer 2 and a Nd-Sb-SnO2 intermediate layer 3; the microscopic surface morphology of the titanium-based multi-component composite anode is composed of a small hill structure, and the hills are densely arranged.
[0008] The raw materials of the TiTa intermediate layer 2 include tantalum pentachloride and tetrabutyl titanate, and the molar ratio is tantalum pentachloride:tetrabutyl titanate=(20-40):(90-120); the coating thickness of the TiTa intermediate layer 2 is 1-3 μm.
[0009] The raw materials of the Nd-Sb-SnO2 intermediate layer 3 include neodymium trichloride, antimony trichloride and tin tetrachloride. The molar ratio of neodymium trichloride: antimony trichloride: tin tetrachloride = (1-5): (5-10): (90-100); the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 3-5μm.
[0010] The raw materials of the α-PbO2 buffer layer 4 include lead oxide, sodium hydroxide and potassium dichromate, and the molar ratio is lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15); the coating thickness of the α-PbO2 buffer layer 4 is 20-200 μm.
[0011] The raw materials of the Bi-Co3O4-MnO2-PbO2 active layer 5 include lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide and manganese dioxide. Calculated by molar ratio, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = (80-100): (20-60): (1-5): (1-5): (2-9); the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 100-800 μm.
[0012] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0013] Step 1, preparation of TiTa intermediate layer 2:
[0014] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated at 60°C-80°C and stirred for 30min-60min to obtain a sol; the obtained sol is coated on a titanium substrate pretreated by sandblasting and pickling, dried and calcined, and then cooled to room temperature, the drying temperature used is 80°C-100°C, and the drying time is 10-15min; the calcination temperature used is 400-500°C, and the calcination time is 15-20min; the above steps are repeated 3-5 times to obtain a first TiTa intermediate layer 2; according to the molar ratio of the raw materials, tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = (20-40): (90-120): (1-3): (1-3): (1-3);
[0015] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0016] Mix citric acid and ethylene glycol, heat and stir at 60°C-80°C for 30-60min to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C-100°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 90min-120min to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1, dry, calcine, cool to room temperature, the drying temperature used is 130°C-150°C, and dry The time is 20-40min; the calcination temperature is 450-550°C, and the calcination time is 15-25min; the above steps are repeated 6-8 times to obtain the second Nd-Sb-SnO2 intermediate layer 3; according to the molar ratio of the raw materials, citric acid: ethylene glycol = (1-3): (4-14); viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = (1000-1400): (90-100): (5-10): (1-5);
[0017] Step 3, preparing α-PbO2 buffer layer 4:
[0018] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 30-50°C and the current density is 50-200A / m 2 , the deposition time is 0.5-2h; the lead-containing alkaline solution, according to the molar ratio of the raw materials, lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15), the final concentration of lead oxide is 0.10-0.12mol / L;
[0019] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0020] Lead nitrate, copper nitrate, bismuth nitrate, cobalt oxide, manganese dioxide and deionized water are mixed, and the pH is adjusted to 1-2 with nitric acid after ultrasonic treatment for 60min-90min to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for electrodeposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for electrodeposition is 50-70°C, and the current density is 150-450A / m 2 , the deposition time is 1-4h; the multi-component acidic plating solution, according to the molar ratio of the raw materials, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = (80-100): (20-60): (1-5): (1-5): (2-9), and the final concentration of lead nitrate is 0.8-1.0 mol / L.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. In the titanium-based multi-component composite anode provided by the present invention, the introduction of the TiTa layer improves the oxidation resistance of the anode and prevents passivation of the matrix; the Nd-doped Sb-SnO2 layer forms a multi-component solid solution with the matrix to reduce the number of cracks on the anode surface; the TiTa layer and the Nd-Sb-SnO2 layer form a multi-layer intermediate layer through a gradient heat treatment method, which plays a role in the bonding transition between the matrix and the active layer, inhibits the entry of electrolyte and active substances, avoids the formation of a passivation layer, and improves the stability of the composite anode.
[0023] 2. In the present invention, potassium dichromate is added during the electrodeposition of the α-PbO2 buffer layer 4, which is beneficial to improving the uniformity and density of the α-PbO2 buffer layer and enhancing the bonding force between the intermediate layer and the active layer.
[0024] 3. The present invention forms a Bi-Co3O4-MnO2-PbO2 active layer 5 by electrodeposition in a multi-component plating solution, thereby achieving homogeneous doping of multiple components, increasing the number of active sites while refining the grains, reducing the internal stress of the coating, and lowering the oxygen evolution potential of the anode, thereby achieving the purpose of reducing energy consumption.
[0025] 4. The multi-layer titanium-based multi-component composite anode provided by the present invention has significantly enhanced catalytic activity and stability due to the synergistic effect between the layers. During use, the fluorine and chlorine resistance can be improved by more than 2 times, reducing the dissolution rate of the active layer on the anode surface.
[0026] In summary, the present invention utilizes gradient solution heat treatment technology and multi-component collaborative co-deposition technology to prepare a titanium-based multi-component composite anode with multiple intermediate layers, buffer layers and active layers, breaking through the technical bottleneck of electrodes with high catalytic activity, high stability and low energy consumption, significantly improving the stability and catalytic activity of the electrode, reducing the energy consumption of the electrode, extending the service life by more than 2.5 times in the field of non-ferrous metal electrochemical metallurgy, and reducing the cell voltage by 0.5V. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of the titanium-based multi-component composite anode of the present invention.
[0028] Figure 2 is a SEM image of the titanium-based multi-component composite anode prepared in Example 1, wherein: Figure 2 (a) Magnification 500 times; Figure 2 (b) Magnification 2500 times.
[0029] Figure 3 This is the EDS-mapping diagram of the titanium-based multi-component composite anode prepared in Example 1.
[0030] Figure 4 This is the XPS graph of the titanium-based multi-component composite anode prepared in Example 1.
[0031] Figure 5 This is a comparison of the LSV diagrams of the titanium-based multi-component composite anode prepared in Example 1 and the Ti / Sb-SnO2 / PbO2 anode prepared in Comparative Example 1.
[0032] Figure 6 This is a comparison of the EIS graphs of the titanium-based multi-component composite anode prepared in Example 1 and the Ti / Sb-SnO2 / PbO2 anode prepared in Comparative Example 1.
[0033] Figure 7 The lifespans of the titanium-based multi-component composite anodes prepared in Examples 1-5 and the Ti / Sb-SnO2 / PbO2 anode prepared in Comparative Example 1 are compared.
[0034] Figure 8 The cell pressure changes of the titanium-based multi-component composite anodes prepared in Examples 1-5 and the Ti / Sb-SnO2 / α-PbO2 / PbO2 anode prepared in Comparative Example 2 during simulated zinc electrowinning. DETAILED DESCRIPTION
[0035] The technical solution adopted by the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0036] like Figure 1As shown, a low-energy consumption and long-life titanium-based multi-component composite anode includes, from bottom to top, a titanium matrix layer 1, a multi-layer intermediate layer, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein, the multi-layer intermediate layer includes, from bottom to top, a TiTa intermediate layer 2 and a Nd-Sb-SnO2 intermediate layer 3; the microscopic surface morphology of the titanium-based multi-component composite anode is composed of a small hill structure, and the hills are densely arranged, which effectively blocks the electrolyte from penetrating into the matrix, while increasing the number of active sites on the electrode surface, significantly improving the stability and catalytic activity of the electrode.
[0037] The raw materials of the TiTa intermediate layer 2 include tantalum pentachloride and tetrabutyl titanate, and the molar ratio is tantalum pentachloride:tetrabutyl titanate=(20-40):(90-120); the coating thickness of the TiTa intermediate layer 2 is 1-3 μm.
[0038] The raw materials of the Nd-Sb-SnO2 intermediate layer 3 include neodymium trichloride, antimony trichloride and tin tetrachloride. The molar ratio of neodymium trichloride: antimony trichloride: tin tetrachloride = (1-5): (5-10): (90-100); the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 3-5μm.
[0039] The raw materials of the α-PbO2 buffer layer 4 include lead oxide, sodium hydroxide and potassium dichromate, and the molar ratio is lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15); the coating thickness of the α-PbO2 buffer layer 4 is 20-200 μm.
[0040] The raw materials of the Bi-Co3O4-MnO2-PbO2 active layer 5 include lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide and manganese dioxide. Calculated by molar ratio, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = (80-100): (20-60): (1-5): (1-5): (2-9); the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 100-800 μm.
[0041] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0042] Step 1, preparation of TiTa intermediate layer 2:
[0043] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated and stirred at 60°C-80°C for 30min-60min to obtain a sol; the obtained sol is coated on the titanium substrate layer 1 which has been pre-treated by sandblasting and pickling, dried and calcined, and then cooled to room temperature, the drying temperature used is 80°C-100°C, and the drying time is 10-15min; the calcination temperature used is 400-500°C, and the calcination time is 15-20min; the above steps are repeated 3-5 times to obtain the first TiTa intermediate layer 2;
[0044] In the step 1, the molar ratio of the raw materials is: tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = (20-40): (90-120): (1-3): (1-3): (1-3).
[0045] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0046] Mix citric acid and ethylene glycol, heat and stir at 60°C-80°C for 30-60min to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C-100°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and magnetically stir for 90min-120min to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1, dry, calcine, and cool to room temperature, the drying temperature used is 130°C-150°C, and the drying time is 20-40min; the calcination temperature used is 450-550°C, and the calcination time is 15-25min; repeat the above steps 6-8 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0047] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = (1-3): (4-14); viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = (1000-1400): (90-100): (5-10): (1-5).
[0048] Step 3, preparing α-PbO2 buffer layer 4:
[0049] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 30-50°C and the current density is 50-200A / m 2 , the deposition time is 0.5-2h;
[0050] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15) based on the raw materials, and the final concentration of lead oxide is 0.10-0.12 mol / L.
[0051] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0052] Lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 60min-90min, and then the pH is adjusted to 1-2 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for electrodeposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for electrodeposition is 50-70°C, and the current density is 150-450A / m 2 , the deposition time is 1-4h.
[0053] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide of (80-100): (20-60): (1-5): (1-5): (2-9) according to the raw materials, and the final concentration of lead nitrate is 0.8-1.0 mol / L.
[0054] The titanium-based multi-component composite anode prepared by the invention has good bonding strength with the titanium matrix, low cell pressure, extended service life by more than 2.5 times, and reduced cell pressure by 0.5 V. The titanium-based multi-component composite anode of the invention has good corrosion resistance and strong stability in the field of non-ferrous metal electrochemical metallurgy.
[0055] Example 1
[0056] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a TiTa intermediate layer 2, a Nd-Sb-SnO2 intermediate layer 3, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the coating thickness of the TiTa intermediate layer 2 is 2 μm; the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 4 μm; the coating thickness of the α-PbO2 buffer layer 4 is 200 μm; and the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 400 μm.
[0057] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0058] Step 1, preparation of TiTa intermediate layer 2:
[0059] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol were mixed, heated at 60°C and stirred for 60 minutes to obtain a sol; the obtained sol was coated on the titanium substrate layer 1 which had been pre-treated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature, the drying temperature used was 80°C, and the drying time was 15 minutes; the calcination temperature used was 450°C, and the calcination time was 15 minutes; the above steps were repeated 4 times to obtain the first TiTa intermediate layer 2;
[0060] In the step 1, the molar ratio of the raw materials is tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = 30:100:1:1:1.
[0061] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0062] Mix citric acid and ethylene glycol, heat and stir at 60°C for 60 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 90 minutes to obtain a coating solution; apply the obtained coating solution to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature, the drying temperature used is 130°C, and the drying time is 30 minutes; the calcination temperature used is 500°C, and the calcination time is 20 minutes; repeat the above steps 7 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0063] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = 3:10; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1400:100:10:3.
[0064] Step 3, preparing α-PbO2 buffer layer 4:
[0065] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 40°C and the current density is 150A / m 2 , the deposition time is 1.5h; the addition of potassium dichromate is beneficial to improving the uniformity and density of the α-PbO2 buffer layer;
[0066] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = 100:350:5 according to the raw materials, and the final concentration of lead oxide is 0.10 mol / L.
[0067] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0068] Lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 90 minutes, and then the pH is adjusted to 1 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h;
[0069] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate: copper nitrate: bismuth nitrate: cobalt oxide: manganese dioxide of 90:50:1:1:2, and the final concentration of lead nitrate is 0.9 mol / L.
[0070] Example 2
[0071] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a TiTa intermediate layer 2, a Nd-Sb-SnO2 intermediate layer 3, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the coating thickness of the TiTa intermediate layer 2 is 3 μm; the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 5 μm; the coating thickness of the α-PbO2 buffer layer 4 is 200 μm; and the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 800 μm.
[0072] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0073] Step 1, preparation of TiTa intermediate layer 2:
[0074] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated at 80°C and stirred for 30 minutes to obtain a sol; the obtained sol is coated on the titanium substrate layer 1 which has been pre-treated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature, the drying temperature used is 100°C, and the drying time is 10 minutes; the calcination temperature used is 400°C, and the calcination time is 20 minutes; the above steps are repeated 5 times to obtain the first TiTa intermediate layer 2;
[0075] In the step 1, the molar ratio of the raw materials is tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = 40:120:3:3:3.
[0076] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0077] Mix citric acid and ethylene glycol, heat and stir at 80°C for 30 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 100°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 100 minutes to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature, the drying temperature used is 150°C, and the drying time is 20 minutes; the calcination temperature used is 450°C, and the calcination time is 25 minutes; repeat the above steps 8 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0078] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = 3:14; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1400:100:10:5.
[0079] Step 3, preparing α-PbO2 buffer layer 4:
[0080] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4. The electrodeposition temperature is 50°C and the current density is 200A / m 2 , the deposition time is 2h; the addition of potassium dichromate is beneficial to improving the uniformity and density of the α-PbO2 buffer layer;
[0081] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = 100:350:3 according to the raw materials, and the final concentration of lead oxide is 0.12 mol / L.
[0082] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0083] Lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 60 minutes, and then the pH is adjusted to 2 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 70°C, and the current density is 450A / m 2 , the deposition time is 4h;
[0084] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide and manganese dioxide of 80:20:1:1:2, and the final concentration of lead nitrate is 1.0 mol / L.
[0085] Example 3
[0086] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a TiTa intermediate layer 2, a Nd-Sb-SnO2 intermediate layer 3, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the coating thickness of the TiTa intermediate layer 2 is 1 μm; the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 3 μm; the coating thickness of the α-PbO2 buffer layer 4 is 20 μm; and the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 100 μm.
[0087] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0088] Step 1, preparation of TiTa intermediate layer 2:
[0089] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol were mixed, heated and stirred at 70°C for 50 minutes to obtain a sol; the obtained sol was coated on the titanium substrate layer 1 which had been pre-treated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature; the drying temperature used was 90°C, and the drying time was 12 minutes; the calcination temperature used was 500°C, and the calcination time was 17 minutes; the above steps were repeated 3 times to obtain the first TiTa intermediate layer 2;
[0090] In the step 1, the molar ratio of the raw materials is tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = 30:110:3:2:2.
[0091] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0092] Mix citric acid and ethylene glycol, heat and stir at 70°C for 50 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 95°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 100 minutes to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature; the drying temperature used is 140°C, and the drying time is 30 minutes; the calcination temperature used is 550°C, and the calcination time is 20 minutes; repeat the above steps 6 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0093] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = 2:11; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1300:95:9:3.
[0094] Step 3, preparing α-PbO2 buffer layer 4:
[0095] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 30°C and the current density is 50A / m 2 , the deposition time is 0.5h; the addition of potassium dichromate is beneficial to improving the uniformity and density of the α-PbO2 buffer layer;
[0096] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = 120:420:15 according to the raw materials, and the final concentration of lead oxide is 0.10 mol / L.
[0097] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0098] Lead nitrate, copper nitrate, bismuth nitrate, cobalt oxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 80 minutes, and then the pH is adjusted to 1.5 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 50°C, and the current density is 450A / m 2 , the deposition time is 1h;
[0099] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate: copper nitrate: bismuth nitrate: cobalt oxide: manganese dioxide of 100:60:5:5:9, and the final concentration of lead nitrate is 0.8 mol / L.
[0100] Example 4
[0101] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a TiTa intermediate layer 2, a Nd-Sb-SnO2 intermediate layer 3, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the coating thickness of the TiTa intermediate layer 2 is 2 μm; the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 4 μm; the coating thickness of the α-PbO2 buffer layer 4 is 150 μm; and the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 450 μm.
[0102] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0103] Step 1, preparation of TiTa intermediate layer 2:
[0104] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol were mixed, heated and stirred at 60°C for 30 minutes to obtain a sol; the obtained sol was coated on the titanium substrate layer 1 which had been pre-treated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature; the drying temperature used was 80°C, and the drying time was 15 minutes; the calcination temperature used was 425°C, and the calcination time was 18 minutes; the above steps were repeated 4 times to obtain the first TiTa intermediate layer 2;
[0105] In the step 1, the molar ratio of the raw materials is tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = 20:90:1:1:1.
[0106] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0107] Mix citric acid and ethylene glycol, heat and stir at 80°C for 30 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 100 minutes to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature; the drying temperature used is 130°C, and the drying time is 30 minutes; the calcination temperature used is 475°C, and the calcination time is 20 minutes; repeat the above steps 7 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0108] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = 1:4; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1000:90:5:1.
[0109] Step 3, preparing α-PbO2 buffer layer 4:
[0110] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 40°C and the current density is 150A / m 2 , the deposition time is 1.5h; the addition of potassium dichromate is beneficial to improving the uniformity and density of the α-PbO2 buffer layer;
[0111] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = 110:400:9 according to the raw materials, and the final concentration of lead oxide is 0.11 mol / L.
[0112] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0113] Lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 90 minutes, and then the pH is adjusted to 1 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h;
[0114] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide of 90:50:3:3:5, and the final concentration of lead nitrate is 0.9 mol / L.
[0115] Example 5
[0116] A low-energy consumption and long-life titanium-based multi-component composite anode comprises, from bottom to top, a titanium base layer 1, a TiTa intermediate layer 2, a Nd-Sb-SnO2 intermediate layer 3, an α-PbO2 buffer layer 4 and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein the coating thickness of the TiTa intermediate layer 2 is 1 μm; the coating thickness of the Nd-Sb-SnO2 intermediate layer 3 is 5 μm; the coating thickness of the α-PbO2 buffer layer 4 is 150 μm; and the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer 5 is 450 μm.
[0117] A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode comprises the following steps:
[0118] Step 1, preparation of TiTa intermediate layer 2:
[0119] Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated at 80°C and stirred for 30 minutes to obtain a sol; the obtained sol is coated on the titanium substrate layer 1 which has been pre-treated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature; the drying temperature used is 100°C, and the drying time is 10 minutes; the calcination temperature used is 450°C, and the calcination time is 15 minutes; the above steps are repeated 3 times to obtain the first TiTa intermediate layer 2;
[0120] In the step 1, the molar ratio of the raw materials is 40:90:3:3:3 for tantalum pentachloride:tetrabutyl titanate:ethanol:isopropanol:n-butanol.
[0121] Step 2, preparation of Nd-Sb-SnO2 intermediate layer 3:
[0122] Mix citric acid and ethylene glycol, heat and stir at 60°C for 60 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 100°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 100 minutes to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature; the drying temperature used is 130°C, and the drying time is 40 minutes; the calcination temperature used is 550°C, and the calcination time is 15 minutes; repeat the above steps 8 times to obtain a second Nd-Sb-SnO2 intermediate layer 3;
[0123] In the step 2, according to the molar ratio of the raw materials, citric acid: ethylene glycol = 3:4; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1400:90:5:1.
[0124] Step 3, preparing α-PbO2 buffer layer 4:
[0125] The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer 4; the electrodeposition temperature is 40°C and the current density is 150A / m 2 , the deposition time is 1.5h; the addition of potassium dichromate is beneficial to improving the uniformity and density of the α-PbO2 buffer layer;
[0126] In step 3, the lead-containing alkaline solution has a molar ratio of lead oxide: sodium hydroxide: potassium dichromate = 110:420:3 according to the raw materials, and the final concentration of lead oxide is 0.11 mol / L.
[0127] Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer 5:
[0128] Lead nitrate, copper nitrate, bismuth nitrate, cobalt oxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 60 minutes, and then the pH is adjusted to 2 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer 5, and the electrode obtained after washing and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h;
[0129] In step 4, the multi-component acidic plating solution has a molar ratio of lead nitrate: copper nitrate: bismuth nitrate: cobalt oxide: manganese dioxide of 90:60:5:5:2, and the final concentration of lead nitrate is 0.9 mol / L.
[0130] Comparative Example 1
[0131] This case is a comparative example, which is an undoped modified Ti / Sb-SnO2 / PbO2 anode. The steps are as follows:
[0132] Step 1, mixing citric acid and ethylene glycol, heating and stirring at 60°C for 60 minutes to obtain a viscous polymer precursor solution; heating the viscous polymer precursor solution to 90°C, adding tin tetrachloride and antimony trichloride, and magnetically stirring for 90 minutes to obtain a coating liquid; coating the prepared coating liquid on a titanium substrate that has been pretreated by sandblasting and pickling, drying, calcining, and then cooling to room temperature; the drying temperature used is 130°C, and the drying time is 30 minutes; the calcination temperature used is 500°C, and the calcination time is 20 minutes; repeating the above steps 7 times to obtain a Sb-SnO2 intermediate layer;
[0133] In the step 1, according to the molar ratio, citric acid: ethylene glycol = 3:10; viscous polymer precursor solution: tin tetrachloride: antimony trichloride = 1400:100:10.
[0134] Step 2, mixing lead nitrate, copper nitrate and deionized water, ultrasonicating at 100% ultrasonic power for 90 minutes, and adjusting the pH to 1 with nitric acid to form an acidic plating solution; wherein the molar ratio of lead nitrate to copper nitrate is 90:50, and the final concentration of lead nitrate is 0.9 mol / L; placing the sample prepared in step 1 in the acidic plating solution for electrodeposition to obtain a PbO2 active layer, and washing and drying to obtain an electrode, namely a Ti / Sb-SnO2 / PbO2 anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h.
[0135] Comparative Example 2
[0136] This case is a comparative example, which is an undoped modified Ti / Sb-SnO2 / α-PbO2 / PbO2 anode with an α-PbO2 buffer layer added. The steps are as follows:
[0137] Step 1, mixing citric acid and ethylene glycol, heating and stirring at 60°C for 60 minutes to obtain a viscous polymer precursor solution; heating the viscous polymer precursor solution to 90°C, adding tin tetrachloride and antimony trichloride, and magnetically stirring for 90 minutes; coating the obtained coating liquid on a titanium substrate that has been pretreated by sandblasting and pickling, drying, calcining, and then cooling to room temperature; the drying temperature used is 130°C, and the drying time is 30 minutes; the calcination temperature used is 500°C, and the calcination time is 20 minutes; repeating the above steps 7 times to obtain a Sb-SnO2 intermediate layer;
[0138] In the step 1, according to the molar ratio, citric acid: ethylene glycol = 3:10; viscous polymer precursor solution: tin tetrachloride: antimony trichloride = 1400:100:10.
[0139] Step 2, placing the sample prepared in step 1 in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer; the molar ratio of lead oxide, sodium hydroxide and potassium dichromate used is 100:350:5, and the final concentration of lead oxide is 0.10 mol / L; the temperature used for electrodeposition is 40°C, and the current density is 150A / m 2 , the deposition time is 1.5h.
[0140] Step 3, mixing lead nitrate, copper nitrate and deionized water, ultrasonicating at 100% ultrasonic power for 90 minutes, and adjusting the pH to 1 with nitric acid to form an acidic plating solution; wherein the molar ratio of lead nitrate to copper nitrate is 90:50, and the final concentration of lead nitrate is 0.9 mol / L; placing the sample prepared in step 2 in the acidic plating solution for electrodeposition to obtain a PbO2 active layer, and washing and drying to obtain an electrode, namely a Ti / Sb-SnO2 / α-PbO2 / PbO2 anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h.
[0141] like Figure 1 The figure shows a schematic diagram of the titanium-based multi-component composite anode structure of Example 1 of the present invention. From bottom to top, it includes a titanium matrix layer 1, a multi-layer intermediate layer, an α-PbO2 buffer layer 4, and a Bi-Co3O4-MnO2-PbO2 active layer 5; wherein, the multi-layer intermediate layer includes a TiTa intermediate layer 2 and a Nd-Sb-SnO2 intermediate layer 3 from bottom to top; the microscopic surface morphology of the titanium-based multi-component composite anode is composed of a small hill structure, and the hills are densely arranged, which effectively blocks the electrolyte from penetrating into the matrix, while increasing the number of active sites on the electrode surface, significantly improving the stability and catalytic activity of the electrode.
[0142] Figure 2-Figure 4 The SEM, EDS-mapping and XPS images of the titanium-based multi-component composite anode prepared in Example 1 show that the surface rhombic structure of the titanium-based multi-component composite anode is dense. The EDS-mapping and XPS images further confirm the presence of Bi, Co and Mn elements, and each element is evenly distributed on the anode surface.
[0143] Figure 5 and Figure 6The LSV and EIS of the titanium-based multi-component composite anode prepared in Example 1 are compared with the Ti / Sb-SnO2 / PbO2 anode prepared in Comparative Example 1. It can be seen from the figure that the oxygen evolution potential and electrochemical impedance of the titanium-based multi-component composite anode after doping and modification are significantly reduced, indicating that the charge transfer capacity of the titanium-based multi-component composite anode is enhanced and the energy consumption is reduced during the electrodeposition process.
[0144] Figure 7 The lifespan of the titanium-based multi-component composite anodes prepared in Examples 1-5 is compared with the Ti / Sb-SnO2 / PbO2 anode prepared in Comparative Example 1. It can be seen from the figure that the lifespan of the titanium-based multi-component composite anodes prepared in Examples 1-5 is significantly improved compared with that of Comparative Example 1, and their service life is increased by more than 2.5 times.
[0145] Figure 8 The cell voltage changes of the titanium-based multi-component composite anodes prepared in Examples 1-5 and the Ti / Sb-SnO2 / α-PbO2 / PbO2 anode prepared in Comparative Example 2 during simulated zinc electrowinning. It can be seen from the figure that the cell voltage of the titanium-based multi-component composite anodes prepared in Examples 1-5 is lower than that in Comparative Example 2, and the cell voltage is reduced by 0.5V.
[0146] The above is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be obvious to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. It should be understood that the present invention is not limited to the above-described content, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A low energy consumption and long life titanium-based multi-component composite anode, characterized in that: From bottom to top, it includes a titanium matrix layer (1), a multi-layer intermediate layer, an α-PbO2 buffer layer (4) and a Bi-Co3O4-MnO2-PbO2 active layer (5); wherein the multi-layer intermediate layer includes, from bottom to top, a TiTa intermediate layer (2) and a Nd-Sb-SnO2 intermediate layer (3); the microscopic surface morphology of the titanium-based multi-component composite anode is composed of a small hill structure, and the hills are densely arranged.
2. The low-energy-consumption and long-life titanium-based multi-component composite anode according to claim 1, characterized in that: The raw materials of the TiTa intermediate layer (2) include tantalum pentachloride and tetrabutyl titanate, and the molar ratio is tantalum pentachloride:tetrabutyl titanate=(20-40):(90-120); the coating thickness of the TiTa intermediate layer (2) is 1-3 μm.
3. The low-energy-consumption and long-life titanium-based multi-component composite anode according to claim 1, characterized in that: The raw materials of the Nd-Sb-SnO2 intermediate layer (3) include neodymium trichloride, antimony trichloride and tin tetrachloride. According to the molar ratio, neodymium trichloride: antimony trichloride: tin tetrachloride = (1-5): (5-10): (90-100); the coating thickness of the Nd-Sb-SnO2 intermediate layer (3) is 3-5 μm.
4. The low-energy-consumption and long-life titanium-based multi-component composite anode according to claim 1, characterized in that: The raw materials of the α-PbO2 buffer layer (4) include lead oxide, sodium hydroxide and potassium dichromate, and the molar ratio is lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15); the coating thickness of the α-PbO2 buffer layer (4) is 20-200 μm.
5. The low-energy-consumption and long-life titanium-based multi-component composite anode according to claim 1, characterized in that: The raw materials of the Bi-Co3O4-MnO2-PbO2 active layer (5) include lead nitrate, copper nitrate, bismuth nitrate, cobalt tetroxide and manganese dioxide. According to the molar ratio, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = (80-100): (20-60): (1-5): (1-5): (2-9); the coating thickness of the Bi-Co3O4-MnO2-PbO2 active layer (5) is 100-800 μm.
6. A method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode, characterized in that: The following steps are involved: Step 1, preparing a TiTa intermediate layer (2): Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated at 60°C-80°C and stirred for 30min-60min to obtain a sol; the obtained sol is coated on a titanium substrate layer (1) pretreated by sandblasting and pickling, dried, calcined, and then cooled to room temperature, the drying temperature used is 80°C-100°C, and the drying time is 10-15min; the calcination temperature used is 400-500°C, and the calcination time is 15-20min; Repeat the above steps 3-5 times to obtain the first TiTa intermediate layer (2); according to the molar ratio of the raw materials, tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = (20-40): (90-120): (1-3): (1-3): (1-3); Step 2, preparing Nd-Sb-SnO2 intermediate layer (3): Mix citric acid and ethylene glycol, heat and stir at 60°C-80°C for 30-60min to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C-100°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 90min-120min to obtain a coating liquid; apply the obtained coating liquid to the sample treated in step 1, dry, calcine, and cool to room temperature. The drying temperature used is 130°C-150°C, and the drying time is 20min-300min. The calcination temperature is 450-550°C and the calcination time is 15-25min. The above steps are repeated 6-8 times to obtain the second Nd-Sb-SnO2 intermediate layer (3). According to the molar ratio of the raw materials, citric acid: ethylene glycol = (1-3): (4-14); viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = (1000-1400): (90-100): (5-10): (1-5); Step 3, preparing an α-PbO2 buffer layer (4): The sample obtained in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer (4); the electrodeposition temperature is 30-50°C and the current density is 50-200A / m 2 , the deposition time is 0.5-2h; the lead-containing alkaline solution, according to the molar ratio of the raw materials, lead oxide: sodium hydroxide: potassium dichromate = (100-120): (350-420): (3-15), the final concentration of lead oxide is 0.10-0.12mol / L; Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer (5): Lead nitrate, copper nitrate, bismuth nitrate, cobalt oxide, manganese dioxide and deionized water are mixed, and after ultrasonic treatment for 60 minutes to 90 minutes, the pH value is adjusted to 1-2 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for electrodeposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer (5); the electrode obtained after washing with water and drying is the titanium-based multi-component composite anode; the temperature used for the electrodeposition is 50-70°C, and the current density is 150-450A / m 2 , the deposition time is 1-4h; the multi-component acidic plating solution, according to the molar ratio of the raw materials, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = (80-100): (20-60): (1-5): (1-5): (2-9), and the final concentration of lead nitrate is 0.8-1.0 mol / L.
7. The method for preparing a low-energy-consumption and long-life titanium-based multi-component composite anode according to claim 6, characterized in that: The following steps are involved: Step 1, preparing a TiTa intermediate layer (2): Tantalum pentachloride, tetrabutyl titanate, ethanol, isopropanol and n-butanol are mixed, heated at 60°C and stirred for 60 minutes to obtain a sol; the obtained sol is coated on a titanium substrate layer (1) pretreated by sandblasting and pickling by an immersion pulling method, dried, calcined, and then cooled to room temperature, the drying temperature used is 80°C, and the drying time is 15 minutes; the calcination temperature used is 450°C, and the calcination time is 15 minutes; the above steps are repeated 4 times to obtain a first TiTa intermediate layer (2); according to the molar ratio of the raw materials, tantalum pentachloride: tetrabutyl titanate: ethanol: isopropanol: n-butanol = 30:100:1:1:1; Step 2, preparing Nd-Sb-SnO2 intermediate layer (3): Mix citric acid and ethylene glycol, heat and stir at 60°C for 60 minutes to obtain a viscous polymer precursor solution; heat the viscous polymer precursor solution to 90°C, add neodymium trichloride, tin tetrachloride and antimony trichloride, and stir magnetically for 90 minutes to obtain a coating solution; apply the obtained coating solution to the sample treated in step 1 by an immersion pulling method, dry, calcine, and cool to room temperature, the drying temperature used is 130°C, and the drying time is 30 minutes; the calcination temperature used is 500°C, and the calcination time is 20 minutes; repeat the above steps 7 times to obtain a second Nd-Sb-SnO2 intermediate layer (3); according to the molar ratio of the raw materials, citric acid: ethylene glycol = 3:10; viscous polymer precursor solution: tin tetrachloride: antimony trichloride: neodymium trichloride = 1400:100:10:3; Step 3, preparing an α-PbO2 buffer layer (4): The sample prepared in step 2 is placed in a lead-containing alkaline solution of lead oxide, sodium hydroxide and potassium dichromate for electrodeposition to obtain an α-PbO2 buffer layer (4); the electrodeposition temperature is 40°C and the current density is 150A / m 2 , the deposition time is 1.5h; the lead-containing alkaline solution, according to the molar ratio of the raw materials, lead oxide: sodium hydroxide: potassium dichromate: =100:350:5, the final concentration of lead oxide is 0.10mol / L; Step 4, preparing Bi-Co3O4-MnO2-PbO2 active layer (5): Lead nitrate, copper nitrate, bismuth nitrate, cobalt oxide, manganese dioxide and deionized water are mixed, ultrasonicated at 100% ultrasonic power for 90 minutes, and then the pH is adjusted to 1 with nitric acid to form a multi-component acid plating solution; the sample prepared in step 3 is placed in the multi-component acid plating solution for co-deposition to obtain a Bi-Co3O4-MnO2-PbO2 active layer (5); the electrode obtained after washing with water and drying is a titanium-based multi-component composite anode; the temperature used for co-deposition is 65°C, and the current density is 300A / m 2 , the deposition time is 2h; the multi-component acidic plating solution, according to the molar ratio of the raw materials, lead nitrate: copper nitrate: bismuth nitrate: cobalt tetroxide: manganese dioxide = 90:50:1:1:2, and the final concentration of lead nitrate is 0.9mol / L.
Citation Information
Patent Citations
Titanium-based lead dioxide / manganese dioxide gradient electrode for zinc electrodeposition and preparation method thereof
CN107723747A
A titanium-based gradient lead dioxide composite electrode material for copper electrowinning and a preparation method thereof
CN113862759B